2010
DOI: 10.1016/j.jadohealth.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Predictors of Change in Number of Sexual Partners across Adolescence and Early Adulthood

Abstract: Purpose-Although sexual risk behavior has negative consequences in adolescence and early adulthood, little is known about pathways of sexual risk across development and their correlates. Study goals were to examine trajectories of number of sexual partners across adolescence and into early adulthood, and to investigate hypothesized individual and family-level predictors.Methods-A subset of 8,707 White, Black, and Mexican American participants in the National Longitudinal Study of Adolescent Health reported on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 22 publications
1
49
0
5
Order By: Relevance
“…47 Furthermore, some researchers have posited that other aspects of positive parenting are more influential than monitoring 11 in mitigating risk for HRSB. These have included parental warmth, 48 parentchild communication, 49 and relationship quality, 50 which have all been linked to decreased rates of HRSBs. Future research should investigate whether these dimensions of positive parenting are influential in reducing rates of HRSB among low-income, urban adolescent males when multiple domains of risk are taken into account.…”
Section: Figurementioning
confidence: 99%
“…47 Furthermore, some researchers have posited that other aspects of positive parenting are more influential than monitoring 11 in mitigating risk for HRSB. These have included parental warmth, 48 parentchild communication, 49 and relationship quality, 50 which have all been linked to decreased rates of HRSBs. Future research should investigate whether these dimensions of positive parenting are influential in reducing rates of HRSB among low-income, urban adolescent males when multiple domains of risk are taken into account.…”
Section: Figurementioning
confidence: 99%
“…11,14,16 Other studies have shown that our measure of pregnancy desire (positive or ambivalent feelings about a future hypothetical pregnancy) is associated with pregnancy risk markers among female adolescents, 25,42 including reduced contraceptive use 15,38,40 and an increased risk of pregnancy 6 months 15 and 18 months 26 after a desire for pregnancy has been reported.…”
Section: Discussionmentioning
confidence: 92%
“…Another study [14], showed similar variation in different risk factors associated with number of sexual partners between ages 11 and 27 yearsdpermissive maternal attitudes toward sex, low family warmth, and high motivation to have sex among youth were linked to number of sexual partners at age of 17 years; however, these predictors were not consistently linked with number of sexual partners in young adulthood. Existing research shows positive impact of single-behavior prevention programs with young adults [15,16], including brief targeted interventions [17].…”
Section: Exploring Other Time-varying Predictors For Young Adultsmentioning
confidence: 88%
“…Existing research shows positive impact of single-behavior prevention programs with young adults [15,16], including brief targeted interventions [17]. Nonetheless, data from Vasilenko and Lanza [5] and Kan et al [14] underscore the value of future research exploring time-varying predictors among the early adulthood age group to increase the precision and tailoring of prevention interventions.…”
Section: Exploring Other Time-varying Predictors For Young Adultsmentioning
confidence: 99%